Enhanced Ethanol Production by High Temperature-Tolerance Mutant Pichia kudriavzevii T-T2 in various Carbon and Nitrogen Sources - Monica Ina Martha; Rika Indri Astuti; Wulan Tri Wahyuni (Indonesian Society for microbiology, 2020)
Previously, we had constructed proline accumulating Pichia kudriavzevii yeast mutant (T-T2) that exhibited high temperature tolerance phenotype. In this study we then analyzed the ethanol production of the particular mutant isolate in various carbon (C) and nitrogen sources (N). Fermentation rate of T-T2 either in 4% glucose or substrate mixture (SM = 2%glucose : 2% xylose) was higher than WT strain. The highest CO2 evolving rate by T-T2 in glucose and SM was 57.0 ml/hour and 51.4 ml/hour, respectively, suggesting that T-T2 was capable of using xylose as C-source. T-T2 resulted significant increase of total evolved CO2 than WT strain in glucose as substrate. T-T2 isolate was capable of producing higher ethanol than its WT strains in various C-sources, including glucose, maltose, sucrose, xylose and SM. However, glucose was found as the most preferable C-source to produce ethanol (3.2%) whereas maltose was the least preferable one. T-T2 was found capable in using inorganic sources (NaNO3) to produce ethanol (2.4%) as compared to other N-sources (urea, (NH4)2SO4, NH4Cl). Ethanol production by T-T2 strain in NaNO3 was 16% higher than its WT strain. This data indicate, that NaNO3 is potentially applied as N source alternative to produce ethanol. Based on our study, mutant strain T-T2 shows higher fermentation rate than its WT strain in various sugar and N-sources. The fact that T-T2 could produce ethanol from SM in a similar fermentation rate to single glucose as substrate, suggesting its potential application in the 2nd generation of bioethanol productions.